Lung transplant waitlist outcomes in the United States and patient travel distance. Issue 1 (5th August 2020) - Tsuang, Wayne M.; Arrigain, Susana; Lopez, Rocio; Budev, Marie; Schold, Jesse D.
Abstract : There is a broad range of patient travel distances to reach a lung transplant hospital in the United States. Whether patient travel distance is associated with waitlist outcomes is unknown. We present a cohort study of patients listed between January 1, 2006 and May 31, 2017 using the Scientific Registry of Transplant Recipients. Travel distance was measured from the patient's permanent zip code to the transplant hospital using shared access signature URL access to Google Maps, and assessed using multivariable competing risk regression models. There were 22 958 patients who met inclusion criteria. Median travel distance was 69.7 miles. Among patients who traveled > 60 miles, 41.2% bypassed a closer hospital and sought listing at a more distant hospital. In the adjusted models, when compared to patients who traveled ≤60 miles, patients who traveled >360 miles had a 27% lower subhazard ratio (SHR) for waitlist removal (SHR 0.73, 95% confidence interval [CI]: 0.60, 0.89, P  = .002), 16% lower subhazard for waitlist death (SHR 0.84; 95% CI 0.73‐0.95, P  = .07), and 13% increased likelihood for transplant (SHR 1.13, 95% CI: 1.07, 1.20, P  < .001). Many patients bypassed the nearest transplant hospital, and longer patient travel distance was associated with favorable waitlist outcomes. Abstract : Data show that patients listed for lung transplantation travel a median of nearly 70 miles to a transplant hospital, often bypassing a closer option, and that longer travel distances are associated with favorable waitlist outcomes.